PENGARUH KEPEMIMPINAN, MOTIVASI BERPRESTASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN TANAH DATAR - Zendri Zendri; erni masdupi (Jurnal Riset Manajemen Bisnis dan Publik, 2014)
The aim of  this study was to analyze (1) the effect of leadership on achievement motivation, (2) the effect of leadership on job satisfaction, (3) the influence of achievement motivation on job satisfaction, (4) the effect of leadership on performance, (5) the effect of job satisfaction on performance and (6) the effect on the performance of         achievement motivation. The population in this study were all employees BPBDs Tanah Datar (61 employees), based on the formula Slovin, 53 employees selected as respondents. Research techniques is proportional stratified random cluster sampling. Path analysis is used to answer this research, suggests that; leadership significant and positive impact on achievement motivation; influential leadership significant and positive impact on job satisfaction; achievement motivation of significant and positive influence on performance; leadership significant and positive influence on performance; significant effect on job satisfaction and positf on performance; achievement motivation of significant and positive impact on performance. Keywords : Leadership, achievement motivation, satisfaction, performance